Risk Analysis of Solid, Liquid, and B3 Waste Management Using the Failure Mode and Effect Analysis (FMEA) Method at PT Natural Indococonut Organik - Tri Novia Colling (Takaza Innovatix Labs Ltd., 2026)
Industrial waste management is an important aspect in maintaining the sustainability of company operations and preventing environmental pollution. PT Natural Indococonut Organik (PT NICO) produces solid waste, liquid waste, and Hazardous and Toxic Materials (B3) waste that require systematic risk management and control. This study aims to identify the types and sources of waste, describe the waste management system, and analyze the level of waste management risk using the Failure Mode and Effects Analysis (FMEA) method. The study uses a descriptive research type with a case study approach. The research population includes the entire waste management system at PT NICO, while the sample consists of data on types, sources, generation, and waste management systems obtained through observation, interviews, and documentation. The research instruments include observation sheets, interview guidelines, and documentation. Data analysis was carried out descriptively and continued with the FMEA method through assessments of Severity, Occurrence, Detection, and calculation of Risk Priority Number (RPN). The results of the study showed that liquid waste had the largest generation of ±3,328 liters/day, while the risk with the highest RPN value was leakage or seepage of liquid waste (RPN = 112), followed by errors in storing B3 waste (RPN = 96). The conclusion of the study showed that PT NICO's waste management system has been running well, but still requires improvement in the aspects of monitoring, recording waste generation, and risk control so that waste management becomes more effective and sustainable.